Cohort-controlled comparison of umbilical cord blood transplantation using carlecortemcel-L, a single progenitor-enriched cord blood, to double cord blood unit transplantation - Stiff, Patrick J (Biol Blood Marrow Transplant, 2018)
Umbilical cord blood transplantation (UCBT) has a high early mortality rate primarily related to transplanted stem cell dose. To decrease early mortality and enhance engraftment, a portion of selected cord blood units (20-50%) was expanded with cytokines and the copper chelator tetraethylenepentamine (carlecortemcel-L) and transplanted with the un-manipulated fraction after myeloablative conditioning. The primary endpoint was 100 day survival which was compared to a contemporaneous double-unit cord blood transplant (DUCBT) group. We enrolled 101 patients at 25 sites; the DUCBT comparison (n = 295) was selected from international registries using study eligibility criteria. Baseline carlecortemcel-L study group unit nucleated cell (NC) and CD34+ cell dose/kg were 3·06 × 10(7) and 1·64 × 10(5). Median NC and CD34+ fold expansion were 400 and 77, with a mean total CD34/kg infused of 9.7 × 10(5)/kg. The 100 day survival was 84.2% for the carlecortemcel-L study group vs 74.6% for the DUCBT group [odds ratio 0.50 (95% CI 0·26-0.95); p = 0.035]. Survival at day 180 was similar for the two groups; the major cause of death after day 100 was opportunistic infections. Faster median neutrophil (21 vs 28 days; p < 0.0001), and platelet (54 vs 105 days; p =0.008) engraftment was seen in the carlecortemcel-L study group; acute and chronic GVHD rates were similar. In this multi-national comparative study, transplanting expanded CD34+ stem cells from a portion of a single UCB unit, with the remaining un-manipulated fraction improved 100 day survival compared to DUCBT controls while facilitating myeloid and platelet engraftment. This trial was registered at www.clinicaltrials.gov as #NCT00469729.